2015
DOI: 10.1021/acsami.5b07866
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Hybrid Composites for Efficient Thermal Management of Electronic Devices

Abstract: Thermal management has become a critical aspect in next-generation miniaturized electronic devices. Efficient heat dissipation reduces their operating temperatures and insures optimal performance, service life, and efficacy. Shielding against shocks, vibrations, and moisture is also imperative when the electronic circuits are located outdoors. Potting (or encapsulating) them in polymer-based composites with enhanced thermal conductivity (TC) may provide a solution for both thermal management and shielding chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
113
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 40 publications
4
113
0
Order By: Relevance
“…In other words, at f g = 15 wt% and f Cu = 40 wt%, all possible percolation paths of highly conductive fillers including graphene–graphene, graphene–Cu‐NP, and Cu‐NP–Cu‐NP have been formed. These results confirm the existence of an optimum loading fraction for each filler in composites with the binary dissimilar fillers, which has been reported in some studies for other types of fillers . The saturation after an abrupt change demonstrates that the heat transport is dominated by graphene–graphene fillers, and at approximately f Cu = 40 wt% the entire percolated graphene–graphene network of conductive paths has been formed.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In other words, at f g = 15 wt% and f Cu = 40 wt%, all possible percolation paths of highly conductive fillers including graphene–graphene, graphene–Cu‐NP, and Cu‐NP–Cu‐NP have been formed. These results confirm the existence of an optimum loading fraction for each filler in composites with the binary dissimilar fillers, which has been reported in some studies for other types of fillers . The saturation after an abrupt change demonstrates that the heat transport is dominated by graphene–graphene fillers, and at approximately f Cu = 40 wt% the entire percolated graphene–graphene network of conductive paths has been formed.…”
Section: Resultssupporting
confidence: 89%
“…However, a certain range in the size distribution of FLG fillers turned out to be even beneficial. The size distribution of the fillers can result in the “synergistic” effect, characteristic for the fillers of different dimensions . The “synergistic” effects constitutes a stronger enhancement of the thermal conductivity of the composites with the size‐dissimilar binary fillers than with the individual fillers of the same total concentration .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported values of the "intrinsic" thermal conductivity of highquality large graphene layers are in the range from 2000 to 5000 W m −1 K −1 near room temperature (RT). [77,78] One of the conclusions from the reports of the thermal properties of composites with graphene and FLG is that there exists an optimum range of the filler lateral dimensions, thicknesses, and aspect ratios for heat conduction. [64,[67][68][69] Numerous studies reported enhancement of the thermal properties of TIMs and various other composites as a result of incorporation of SLG and FLG.…”
Section: Introductionmentioning
confidence: 99%